5 G communication network signal propagation models - Kolyadenko, Yu.Yu.; Chursanov N.А. (Radiotekhnika, 2021)
The next generation 5G / IMT-2020 technology, like any new technology, brings its own specific features to all aspects related to the practice of its application. One of these particularly important aspects is electromagnetic compatibility. At the stage of preparation for the introduction of 5G radio networks, called NewRadio, it is necessary to take early measures to assess effectively the electromagnetic compatibility conditions for these networks based on a thorough analysis of the features of 5G technology. Correct and accurate assessments of these conditions means successful provision of the electromagnetic compatibility of radio equipment of new networks. The World Radio Communication Conference WRC-15 identified new radio frequency bands for 5G, including centimeter and millimeter wave bands. In general, this RF spectrum is located in three regions: below 1 GHz, 1 GHz to 6 GHz, and above 6 GHz (up to 100 GHz). From the EMC standpoint, the following can be distinguished as the main features of this spectrum: different nature of losses during signal propagation, in particular, a significant influence of additional factors (gases – oxygen, water vapor, etc.) on the level of losses previously unknown in cellular communication. The mathematical model of signal propagation of 5 G communication networks has been developed which takes into account: the attenuation of signals in free space; attenuation of signals caused by the influence of walls and floor slabs, loss of signal energy, when space is filled with various objects; attenuation of signals caused by loss of energy of radio waves, when propagating through rains; signal attenuation due to loss of radio wave energy due to fog; signal attenuation, when propagating through tree leaves, slow and fast random fading.